Active control of building structures under seismic load using a new uniform deformation-based control algorithm. (October 2021) - Karami Mohammadi, R.; Ghamari, Hadi; Noroozinejad Farsangi, Ehsan
Abstract: There are several algorithms for determining control forces of active devices in civil engineering structures. Uniform distribution of deformations theory is a structural concept which mainly focuses on equalizing deformations in order to promote the utilization of ductility capacity of structural elements thereby mitigating damages to a structure. In common active control algorithms, deformation uniformity and reducing damages are barely noted. In this research, a new active control algorithm regarding uniform deformation theory will be proposed. Uniform distribution of Deformation Control (UDC) algorithm consists of a massless optimized Virtual Added linear structure with Pinned connections (VAP) which is added to a desired original structure. This VAP can be treated as an added stiffness matrix. Once the parameters of the VAP were optimized in a manner that the desired responses were obtained from the new integrated structure, then, the new integrated structure is developed and analyzed in each time step. Finally, the VAP beams axial forces are extracted and applied to the original structure as control forces via active control devices such as active tendons. This proposed control algorithm is simple and effective in reducing responses especially drifts, making more uniform thereby reducing structural damages as well as decreasing the required capacity of actuators and the power consumption eventually. High potential and promising performance of the proposed UDC algorithm will be represented through numerical investigation in an office building example. The results are compared with Nonlinear Instantaneous Optimal Control (NIOC) algorithm as a very common active control algorithm for linear and nonlinear structures.